Microscopic aspects of phase transformation in alloys - Clapp, Philip C. (Comisión Nacional de Energía Atómica; Argentina, 1972)
Fil: Clapp, Philip C. Kennecott Copper Corporation. Ledgemont Laboratory; Estados Unidos